In Vitro Activity Comparison of Ceftazidime–Avibactam and Aztreonam–Avibactam Against Bloodstream Infections With Carbapenem-Resistant Organisms in China - Yu, Wei; Xiong, Luying; Luo, Qixia; Chen, Yunbo; Ji, Jinru; Ying, Chaoqun; Liu, Zhiying; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives: The aim of this work was to investigate the activity of ceftazidime-avibactam (CZA) and aztreonam-avibactam (AZA) against bloodstream infections caused by caused by carbapenem-resistant organisms (CROs). Methods: Nonduplicate CROs, including 56 carbapenem-resistant Escherichia coli (CR-Eco), 318 carbapenem-resistant Klebsiella pneumoniae (CR-Kpn), and 65 carbapenem-resistant Pseudomonas aeruginosa (CR-Pae), were collected by Blood Bacterial Resistant Investigation Collaborative System (BRICS) program in China. The minimum inhibitory concentration (MIC) of 24 antibiotics were tested. Carbapenemase genes were amplified for CZA-resistant CROs by PCR. MIC of CZA and AZA were further determined with avibactam at 8 mg/L and 16 mg/L. Results: The resistant rate of polymyxin B against CROs was less 5%. Only one CR-Kpn was resistant to tigecycline. The resistant rates of CZA against CR-Eco, CR-Kpn and CR-Pae were 75.0%, 12.6%, and 18.5%, respectively. MIC90 of AZA against CR-Eco, CR-Kpn and CR-Pae were 2/4 mg/L, 0.5/4 mg/L and 64/4 mg/L. Among CZA-resistant CROs, 42 (100%) CR-Eco, 24 (60%) CR-Kpn and 1 (8.3%) CR-Pae isolates harboured metallo-β-lactamases genes. Increase of avibactam concentration enhanced the susceptibility of CZA and AZA against CROs, especially for CR-Eco and CR-Kpn. Conclusions: In vitro activity of AZA was superior to that of CZA against CR-Eco and CR-Kpn, whereas CZA showed better effect against CR-Pae.